Genetic diagnosis of fetal microcephaly at a single tertiary center in China - Wang, You; Fu, Fang; Lei, Tingying; Zhen, Li; Deng, Qiong; Zhou, Hang; Ma, Chunling; Cheng, Ken; Huang, Ruibin; Li, Ru; Yu, Qiuxia; Li, Lushan; et al. (Frontiers in Genetics, 2023)
Background: Microcephaly (Mic) is a common phenotype in patients with neuropsychiatric problems, usually closely related to genetic causes. However, there are few studies on fetal microcephaly's chromosomal abnormalities and single gene disorders. Objective: We aim to investigate the cytogenetic and monogenic risks of fetal microcephaly and evaluate their pregnancy outcomes. Methods: We performed a clinical evaluation, high-resolution chromosome microarray analysis, and trio whole-exome sequencing performed on 224 fetuses with prenatal microcephaly, and their pregnancy outcome and prognosis were followed in detail. Results: Among 224 cases of prenatal fetal microcephaly, the diagnosis rate was 3.74% (7/187) for CMA and 19.14% (31/162) for trio-WES. By WES, we detected 31 pathogenic or likely pathogenic (P/LP) with phenotypic fetal structural abnormalities and/or intellectual disability from 25 genes in 37 microcephaly fetuses, 19 (61.29%) were de novo variants. The gene variant involved includes the single gene MPCH, which has been reported to be associated with human microcephaly, and HDAC8, TUBGCP6, OSGEP, ZEB2, NIPBL, FANCI, PDHA1, UBE3A, CASK, TUBB2A, PEX1, LAGE3, and PPFIBP1. The higher live birth rate of fetal microcephaly in the isolated group compared to the non-isolated group. [62.9 % (117/186) vs. 31.56% (12/38), P=0.000]. Conclusion: To our knowledge, this is the first and largest prenatal study to use a combined CMA and WES assay for fetal Mic case genetic analysis. Our data suggest that the combined CMA and WES test has a higher diagnostic rate for genetic causes of fetal Mic cases. In addition, this study identified 14 new mutations that expand the disease spectrum of Mic-related genes.